PENGARUH PELATIHAN RONDE KEPERAWATAN TERHADAP KINERJA PERAWAT DALAM ASUHAN KEPERAWATAN DI RS ROYAL PRIMA MEDAN - Juwita Verawati Siahaan; Albiner Siagian; Evi Karota Bukit (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2018)
ABSTRACT Nursing Round is a method in nursing care which is used to increase services for patients and to give input to nurses about nursing care. It can increase nurses’ cognitive, affective, and psycho-motoric performance. The objective of the research was to find out the influence of nursing round training on nurses’ performance in providing nursing care at Royal Prima Hospital, Medan. The research used quasi-experiment and pretest-posttest with control group design. The samples were 64 nurses as the respondents (32 respondents were in the control group and the other 32 respondents were in the intervention group), taken by using purposive sampling technique. Paired T-test and Independent test were used to find out the influence of nursing round on nurses’ performance. The result of the research showed that 40.63% of the respondents had bad performance before the training, and 68.75% of them had good performance after the training. The result of statistic test showed that there was the difference in nurses’ performance in providing nursing care before and after nursing round training (p = 0.00 < 0.05 and mean difference = 27.56). The conclusion was that there was the influence of nursing round training on nurses’ performance in providing nursing care at Royal Prima Hospital, Medan. It is recommended that the hospital management provide training in order that nurses can improve their knowledge and skill so that their performance in providing nursing care becomes optimal. Keywords: nursing round, nurse performance, nursing care